Island queen ebook A novel. - Riley, Vanessa (2024)
"Vanessa Riley's version of the real-life Dorothy Kirwan Thomas legend will make readers fall in love with this overlooked 'hidden' queen." —Kaia Alderson, author of Sisters in Arms A remarkable, sweeping historical novel based on the incredible true-life story of Dorothy Kirwan Thomas, a free Black woman who rose from slavery to become one of the wealthiest and most powerful landowners in the colonial West Indies.  Born into slavery on the tiny Caribbean island of Montserrat, Doll bought her freedom—and that of her sister and her mother—from her Irish planter father and built a legacy of wealth and power as an entrepreneur, merchant, hotelier, and planter that extended from the marketplaces and sugar plantations of Dominica and Barbados to a glittering luxury hotel in Demerara on the South American continent. Vanessa Riley's novel brings Doll to vivid life as she rises above the harsh realities of slavery and colonialism by working the system and leveraging the competing attentions of the men in her life: a restless shipping merchant, Joseph Thomas; a wealthy planter hiding a secret, John Coseveldt Cells; and a roguish naval captain who will later become King William IV of England. From the bustling port cities of the West Indies to the forbidding drawing rooms of London's elite,  Island Queen  is a sweeping epic of an adventurer and a survivor who answered to no one but herself as she rose to power and autonomy against all odds, defying rigid eighteenth-century morality and the oppression of women as well as people of color. It is an unforgettable portrait of a true larger-than-life woman who made her mark on history.